P941 Evaluation of right ventricular contractile reserve with exercise stress echocardiography. (17th January 2020) - Missana, A; Azzolini Jacquin, M; David, C; Baudouy, D; Sartre, B; Sanfiorenzo, C; Wehrlin, C; Sermesant, M; Ferrari, E; Moceri, P
Abstract: : INTRODUCTION Right ventricular (RV) contractile reserve reflects the ability of the RV to adapt to elevated afterload. RV functional response to exercise is challenging but could represent an important prognostic factor, especially in pulmonary arterial hypertension (PAH) patients. We aimed, using exercise stress echocardiography (ESE), to assess different RV contractile reserve evaluation methods in a cohort of PAH patients and controls. METHODS: We prospectively included 12 patients with PAH and 12 healthy volunteers. An ESE (using tilt-table ergometer) was performed in all patients to assess RV function at rest and under peak exercise. Changes in these parameters during exercise were calculated to quantify the RV contractile reserve. 3D RV function as well as peak systolic strain, pulmonary pressures, TAPSE, pulmonary TVI and pulmonary output (using the right ventricular outflow tract diameter) were assessed in all patients. RESULTS: Our patient group was composed by PAH patients, 61.5 ± 14.8 years; mean age of our control group was 29.33 ± 5.5 years. PAH patients achieved an exercise with a mean workload of 69.17 ± 26.4 Watts. There was no complication after the exercise test in all patients. Change in TAPSE was not significantly different between patients and controls (p = 0.17), whereas change in pulmonary TVI, pulmonary output and RV peak systolic strain was highly discriminant (respectively p = 0.03, p = 0.009 and p = 0.0009). Regarding RV contractile reserve parameters, RV end-systolic pressure area ratio (peak/rest) was not statistically different between controls and patients (p = 0.14) whereas change in TAPSE/sPAP, RV peak strain/sPAP, 3D RV EF/sPAP were significantly different (p = 0.005, p= 0.0008, p = 0004). CONCLUSION: Changes in pulmonary output, RV peak systolic strain as well as changes in TAPSE/sPAP but mainly RV peak strain/sPAP, 3D RV EF/sPAP represent consistent and feasible tools to assess RV contractile reserve.